A rare case of neck abscess caused by Salmonella - Sivakumar, Sivaranjani; Rangarajan, Venkatasubramanian; Manikesi, Muralidharan; Nambi, Senthur (International Surgery Journal, 2022)
Neck abscess is a quite common presentation among diabetic patients, but Salmonella causing neck abscess is very uncommon. Salmonella, which is the causative agent for Enteric fever, is also involved in causing systemic and local infections. We present an interesting case of a 60-year-old diabetic male, who had large neck abscess caused by Salmonella.